Low-voltage low-power (LVLP) scalable voltage reference - Zhang, Kangyu (Nanyang Technological University, 2024)
In recent years, with the continuous advancement of integrated circuit, there has been a significant surge in the demand for low voltage design. Voltage references, being integral components in numerous electronic systems, play a pivotal role in ensuring accurate and reliable operation, such as the central processing units (CPU), the low dropout regulators (LDO), the analog-to-digital converters (ADC). It leverages precision voltage generation techniques such as bandgap references, can effectively mitigate voltage variations due to temperature fluctuations and provide stable voltage outputs, thus meeting the stringent requirements of various applications in electronics. Nevertheless, with the shrinking and advancing of the CMOS technology, the conducting voltage of the bipolar transistor limits the decreasing of the input voltage, thus, the sub-threshold MOS voltage reference design has become a trend in the state-of-arts research due to it can cater a lower input voltage.